Health-related quality of life in gastroesophageal reflux patients with noncardiac chest pain: Emphasis on the role of psychological distress - Zhang, Lei (World J Gastroenterol, 2017)
AIM: To investigate the effects of depression and anxiety on health-related quality of life (QoL) in gastroesophageal reflux disease (GERD) patients and those suffering from cardiac (CCP) and noncardiac (NCCP) chest pain in Wuhan, China. METHODS: In this cross-sectional study, a total of 358 consecutive patients with GERD were enrolled in Wuhan, China, of which 176 subjects had complaints of chest pain. Those with chest pain underwent coronary angiography and were divided into a CCP group (52 cases) and NCCP group (124 cases). Validated GERD questionnaires were completed, and the 36-item Short-Form Health Survey and Hospital Anxiety/Depression Scale were used for evaluation of QoL and psychological symptoms, respectively. RESULTS: There were similar ratios and levels of depression and anxiety in GERD with NCCP and CCP. However, the QoL was obviously lower in GERD with CCP than NCCP (48.34 ± 17.68 vs 60.21 ± 20.27, P < 0.01). In the GERD-NCCP group, rather than the GERD-CCP group, the physical and mental QoL were much poorer in subjects with depression and/or anxiety than those without anxiety or depression. Anxiety and depression had strong negative correlations with both physical and mental health in GERD-NCCP (all P < 0.01), but only a weak relationship with mental components of QoL in GERD-CCP. CONCLUSION: High levels of anxiety and depression may be more related to the poorer QoL in GERD patients with NCCP than those with CCP. This highlights the importance of evaluation and management of psychological impact for improving QoL in GERD-NCCP patients.